2015
DOI: 10.3168/jds.2014-8366
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the interservice intervals of dairy cows in the United Kingdom

Abstract: An understanding of the normal estrous-cycle length of the cow is important when managing and monitoring dairy-herd fertility. Although the normal interovulatory interval is widely considered to be 21 d, some studies have found alternative intervals to be more prevalent; previously, most of the variation in interval length was expected to be between cows. The aim of this study was to assess the time between inseminations (interservice interval, ISI) in a large number of dairy cows and to explore possible assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
5
22
0
1
Order By: Relevance
“…Unquestionably, the greatest detriment to cow reproductive performance is embryo loss. Nevertheless, cows that lose their pregnancy may also exhibit alterations in ovarian function leading to delayed estrus expression and re-insemination [4][5][6]. Pregnancy loss may also be responsible, at least in part, for the poor response to synchronization of estrus and ovulation treatments used for previously inseminated non-pregnant cows [7][8][9][10].…”
Section: Introductionmentioning
confidence: 95%
“…Unquestionably, the greatest detriment to cow reproductive performance is embryo loss. Nevertheless, cows that lose their pregnancy may also exhibit alterations in ovarian function leading to delayed estrus expression and re-insemination [4][5][6]. Pregnancy loss may also be responsible, at least in part, for the poor response to synchronization of estrus and ovulation treatments used for previously inseminated non-pregnant cows [7][8][9][10].…”
Section: Introductionmentioning
confidence: 95%
“…As milk yield has increased in high‐producing dairy cows over the past decades, infertility has become a major concern and is now considered to be one of the most significant problems on dairy farms . The replacement rate in the United Kingdom increased from 25% to 33% between 1990 and 2010 .…”
Section: Animal Welfarementioning
confidence: 99%
“…43 As milk yield has increased in high-producing dairy cows over the past decades, infertility has become a major concern and is now considered to be one of the most significant problems on dairy farms. 44,45 The replacement rate in the United Kingdom increased from 25% to 33% between 1990 and 2010. 46 In 2013, the cull rate for cows reached 38% in the US, which translates to an average productive life span of only 2.63 years or 31.6 months.…”
Section: Animal Welfarementioning
confidence: 99%
“…However, with recent work demonstrating marked differences between the reproductive traits of the modern dairy cow and her genetically distant predecessors, it is plausible that these parameters may no longer accurately describe the dairy cow's estrous cycle (Royal et al, 2000;Lopez-Gatius, 2003;Pryce et al, 2004). Indeed, recent work has shown that interservice interval has a mode of 22 d, with an upper range of 28 d (Remnant et al, 2015). However, this data set focused exclusively on interservice interval and did not examine intervals following estrus events with no insemination.…”
Section: Introductionmentioning
confidence: 99%